ANALISIS VARIASI TEMPERATUR LOGAM KATALIS TEMBAGA (Cu) PADA CATALYTIC CONVERTER UNTUK MEREDUKSI EMISI GAS KARBONMONOKSIDA (CO) DAN HIDROKARBON (HC) KENDARAAN BERMOTOR - Sanata, Andi (ROTOR, 2012)
The air pollution rate caused by the vehicles in big cities is now reach the critical limit. It affects the environmental health as well as the financial factors. To reduce the pollutant gas from the vehicle engines emission, a technology is needed. One of the technology is the application of catalytic converterÂ  inside the exhaust emission. A research has been done on 125 cc motorcycle engine to modify its exhaust emission. The catalysts used in this research was made of copper and designed using the honeycomb system with various diameters ( 4, 6, 8, 10, 12 mm). The observation variables are catalyst temperature, CO and HC emission rate. The emission of CO and HC from the sample engine was then compared with the standard emission rates. Result showed that increase of the copper catalyst temperature resulted in decrease ofÂ  CO and HC emission rates. The decrease started to occur for all the catalysts at 225 oC. Optimum convertion efficiency is up to 47,93 % (CO) and 50,36 % (HC). Both optimum efficiency reached at the temperature of 325 oC using 8 mm diametered catalysts. Keywords : air pollutions, honeycomb system catalytic converter, temperature and copper